One Health Investigation of House Crow (Corvus splendens) Mortality Event Linked to the Potential Circulation of H5N1 Virus at Live Bird Markets in Northwestern Bangladesh. (March 2022) - Islam, A.; Islam, S.; Hossain, M.E.; Samad, M.A.; Billah, M.M.; Hassan, M.M.; Flora, M.S.; Rahman, M.Z.R.; Klaassen, M.; Epstein, J.
Abstract : Purpose: Highly pathogenic avian influenza (H5N1) has caused ≥550 reported outbreaks in poultry and wild birds in Bangladesh since 2007. Responding to reports of a crow mortality event in Rajshahi, a multidisciplinary team investigated the crow mortalities to identify the etiologic agent, source of the infection, and characterize the extent of the outbreak between January 15th and February 20th, 2017. Methods & Materials: We surveyed house crow roosts, neighboring poultry farms, and live bird market (LBM) in the outbreaks areas and observed roosting and feeding behavior of crows. We collected cloacal and oropharyngeal swabs from moribund and dead crows (N=58), environmental samples from 12 LBM (N=162), and 14 poultry farms (N=65) as well as samples from 28 severe acute respiratory illness (SARI) patients as part of existing hospital-based influenza surveillance. All samples were tested using specific real-time RT-PCR for influenza virus A (M gene) and followed by subtype H5, H7 and H9, and N1. Results: Ninety-one percent of crows (n=53;95% Confidence Interval (CI): 81-97%) were positive for A/H5N1. Among LBMs samples, 37.6% (n=61, 95%CI: 30-46) were positive for influenza A including 55.7% for H5N1 (n=34), 9.8% for H9N2 (n=6), 4.9% for H5N1/H9N2 (n=3), 29.5% for influenza A/untypable (n=18). Of the poultry farm samples, 10.7% (n=7; 95%CI: 4-21) were positive for influenza A comprising 14.3% of A/H9 (n=1) and 85.7% (n=6) of A/untypable. None of the crow and LBM samples were positive for H7. All human samples were negative for influenza A. Phylogenetic analysis based on the sequence of HA and NA gene suggesting a new reassortant of clade 2.3.2.1a that previously circulated in 2015. Conclusion: Our findings suggest that multiple subtypes of avian influenza viruses are circulating in LBMs without mortality in poultry. Crows may have been infected by consuming dead poultry and their waste. Continued surveillance of both poultry and wild birds is needed for early detection of novel viral introductions, to trace the transmission route, and to reduce public health risks. Improved LBMs biosecurity measures are needed to reduce the risk of influenza virus spillover to wild birds or people in Bangladesh.